Tunable structural and electrical impedance properties of ordered and disordered iron oxide phases for capacitive applications. Issue 14 (1st October 2018) - Shah, Zaheer H.; Riaz, Saira; Atiq, Shahid; Naseem, Shahzad
Abstract: Having extensive knowledge of room temperature and temperature dependent dielectric and impedance properties of iron oxide nanostructures will help in extending the field of application from biomedical sciences to microelectronics industry. This aspect of iron oxide has long been neglected and the attention is mostly focused on magnetic investigations. To explore and extend the field of application of iron oxide this study is focused on detailed investigation of structural as well as temperature dependent (30–210 °C) dielectric along with impedance analysis. Iron oxide nanostructures are prepared using template free oleic acid assisted sol-gel method with variation in molarity of the finally synthesized sol in the range of 0.2–2.0 mM (interval 0.2 mM). Magnetite (Fe3 O4 ) phase is observed at molarity of 0.2 mM whereas, vacancy ordered and disordered maghemite (γ-Fe2 O3 ) phases are observed at molarities of 0.8–1.0 mM and 1.4–2.0 mM, respectively. Dielectric constant of 104.6, 74.5 and 98.43 (log f = 5.0) is observed at molarities of 0.2 mM, 1.0 mM and 2.0 mM for Fe3 O4 and vacancy ordered (Vo ) & disordered (Vd ) γ-Fe2 O3 phase, respectively. Zview software is used for the fitting of Nyquist plots. Fitted data reveals that dielectric constant strongly depends on grain boundary resistance (Rgb ). Activation energy of 0.25 eV and 0.296 eV (log f = 5) is observed for Fe3 O4 and Vd γ-Fe2 O3 phase at 0.2 mM and 2.0 mM molarity of the final iron oxide sol.